Are the benefits of advance care planning for care home residents, as demonstrated by research studies, seen when implemented in a large-scale clinical service offering advance care planning for care home residents as part of Comprehensive Geriatric Assessment (CGA)? - Garden, Gill (2021)
Introduction Care home residents have a short life expectancy and are more likely to have emergency admissions than people of the same age living in the community. Although such admissions may resolve crises, maintain and restore functional and relieve physical and mental distress, there is evidence that hospital admission may be burdensome or detrimental to the health of older people with severe frailty. Furthermore, admission may not reflect their wishes, or those of their families. Advance care planning is a means by which care home residents can express their health care preferences, not only regarding admission to hospital, but also their choices in relation to other aspects of their care.